Nutritional and Antioxidant Activities of Value Added Products Prepared from Syzygium cuminii L. - Devi, Ramala; Das, Priyanka; Singha Dutta, Archana; Barooah, Madhumita; Chandra Sarmah, Tarun (Asian Journal of Chemistry, 2015)
Considering the seasonal abundance and already recognized nutritional and medicinal values of jamun fruit (Syzygium cuminii L.), three different types of value added products of jamun namely, jamun juice, jamun squash prepared using stevia (Stevia rebaudiana) and jamun squash prepared using sugar were made. After 1 week of the preparation of ]products, the total soluble sugar content was found to be the highest (47.38 g/100 mL) in jamun squash prepared using sugar and the lowest (9.60 g/100 mL) in jamun squash prepared using stevia. The nitrogen content (0.136 g/100 mL), calcium content (10.96 mg/100 mL), the potassium content (38 mg/100 mL) and iron content (0.45 mg/100 mL) were found to be the highest in jamun squash prepared using stevia. The phosphorus content was found to be the highest (10.49 mg/100 mL) in jamun juice and the lowest (6.017 mg/100 mL) in jamun squash prepared using sugar. The antioxidant activity measured in terms of DPPH (1,1-diphenyl-2-picrylhydrazyl) inhibition was found to be the highest for jamun juice and the lowest for jamun squash prepared using sugar. The microbial analysis of jamun products during the different periods of storage revealed that the growth of Lactobacillus species was prominent as compared to other microbes. The data showed a decreasing trend of the values as the duration of storage increased.